Elites políticas, constituição e direitos sociais: elite política e a negação do direito social à educação constitucionalmente assegurado no estado de São Paulo de 1989 a 2022. - Celestino, Sebastião (Universidade Federal de São Carlos, 2024)
This work investigates why, three decades after the promulgation of the Constitution of the state of São Paulo in 1989, the law organizing the state's education system determined by its article 238 was not published. As the Law does not present a satisfactory solution for the legislative omission, the This research seeks to demonstrate that political action is a determining factor in the realization of the constitutionally foreseen social right to education. As a main objective, the research aims to point out that the non-decision of the political elite constitutes a decision not to promote the organization of the population's education, by not complying with the constitutional command. Using the case study method in a qualitative approach, it investigates the profile of the political class over three decades, in order to identify the factors that determine the lack of interest in education that leads to legislative omission. To support the research, this work is built on two theoretical bases, namely, constitutionalism, to start from the premise that the fundamental political decision on the creation by law of the education system has already been taken by the derived constituent, and the Theory of the Elites, to demonstrate that the reality of politics denies the promise made formally. Education is not organized by the state, while leading minorities organize themselves to promote the private education of their members, preparing themselves to occupy leadership positions, under the mantle of the moral justification of being the most prepared for these roles. It is argued that this is not a deficiency in the political system, but rather the interests of the ruling elites in not promoting the education of the governed.
Political elites, constitution and social rights: political elite and the denial of the social right to education constitutionally guaranteed in the state of São Paulo from 1989 to 2022.
Keywords: Educação; Elites políticas; Sistema de ensino; Omissão legislativa; Education; Political elites; Education system; Legislative omission; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS